Perancangan Metode Kerja padaProses Penyortiran Udang di PT. XYZ - Albert Limantara; Tanti Octavia (Jurnal Titra, 2013)
PT. XYZ is a company which is engaged in the field of frozen shrimp exporters that produce shrimp sushi, shrimp tempura, and shrimp peeled. The problem that occurs is often failure to achieve the production target in the process of shrimp sorting. The factors that cause the failure of production target’s achieving are production target which is too high and the workers who are slow in the process of sorting. Based on these problems, in this research is undertaken the improvement of production target and the improvement of the movements of the left hand and right hand of workers in doing the sorting. The research concludes that the production target need to be lowered and is undertaken the improvement of the left hand and right hand of workers so that the production target will be achieved and the efficiency reaches 8,81%.